How internal rotation is measured in reverse total shoulder arthroplasty: a systematic review of the literature - Jorge Rojas, MD; Jacob Joseph, BA; Uma Srikumaran, MD; Edward G. McFarland, MD (JSES International, 2020)
Background: Reverse total shoulder arthroplasty (RTSA) can lead to limited postoperative internal rotation (IR). We assessed how IR is measured and reported in the RTSA literature and examined the relationships between these measures and patient-reported ability to perform activities of daily living. Methods: We searched MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials for articles published in English from January 2000 through September 2018 that reported clinical outcomes after RTSA (minimum 12-month follow-up). We included studies reporting IR range of motion (ROM) and/or patient-reported functional outcomes related to IR. We identified 255 studies, 35% of which were excluded because they reported no IR outcome measures, leaving 165 studies for analysis. Results: Studies reported 3 methods of measuring IR ROM: (1) vertebral level (VL) method (ie, the most proximal VL reached by the extended thumb with the arm behind the back), (2) degrees of IR with the arm abducted to 90°, and (3) degrees of IR with the arm in a neutral position. The VL measurement was reported in 89% of studies, but the methods of reporting this measure varied. Only 9% of studies reported functional outcomes related to IR. No study correlated clinical measurements of IR ROM with functional outcomes. Conclusions: Measures and reporting of shoulder IR after RTSA varied widely. This variability makes it difficult to assess associations between postoperativce IR limitation and functional abilities. Standardization of IR measures and reporting is needed to allow meta-analysis of data related to this important outcome.